Positioning Strategy Selera Aceh As Top-Of-Mind Aceh Noodles Brands In Bandung (Pusat Riset dan Inovasi Nasional, 2025)
The Acehnese noodle market in Bandung has become increasingly competitive as more regional specialty brands enter the city’s culinary scene. Selera Aceh is one of the local players offering Acehnese noodles in a café style setting but has not yet become the top of mind brand when consumers think of “Aceh noodles in Bandung”. This study aims to analyse how Selera Aceh can strengthen its brand positioning to reach top of mind status by identifying key factors that shape consumer perceptions, assessing the current brand equity based on Keller’s Customer Based Brand Equity (CBBE) model, and formulating suitable positioning and marketing improvement strategies. A qualitative case study approach was used, drawing on in depth interviews with existing Selera Aceh customers from diverse backgrounds. Thematic analysis was conducted and the resulting themes were mapped onto the CBBE dimensions Brand Salience, Brand Performance, Brand Imagery, Brand Judgements, Brand Feelings, and Brand Resonance while Integrated Marketing Communication (IMC) principles were applied to translate the insights into practical strategic directions. The findings reveal six key themes. Authentic and good Acehnese taste is the main driver of visits and repeat visits, as customers describe the noodles as flavourful, rich in spices, and comparable to eating in Aceh. A cozy, homey, and memorable dining experience further strengthens emotional attachment, while prices are perceived as affordable yet café like, creating strong value for money judgements. Brand awareness is built through multiple channels that is street level visibility, food delivery applications, and social media supported by promotions and community based activities that generate excitement and a sense of belonging. At the same time, respondents highlight brand gaps in visual identity, Acehnese cultural cues, and communication that Acehnese noodles are suitable for all Bandung consumers, not only people from Aceh or Sumatra.